2021
DOI: 10.1002/aoc.6292
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental investigations of new bis (amino triazole) schiff base ligand: Preparation of its UO2(II), Er (III), and La (III) complexes, studying of their antibacterial, anticancer, and molecular docking

Abstract: UO 2 (II), Er (III), and La (III) complexes were prepared from new bis (amino triazole) Schiff base ligand. The ligand was synthesized by condensation of 1,3-bis(4-amino-5-phenyl-1,2,4-triazol-3-ylsulfanyl)propane with benzaldehyde. The structure of the prepared compounds was confirmed by some spectroscopic tools such as 1 H-NMR, UV-Vis, and IR, as well as molar conductance, mass spectrometry, elemental analysis, thermogravimetric analysis (TG), differential thermogravimetric (DTG), and differential thermal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…The results clarified that uranyl complexes show better anticancer activities than ligands when both cells are examined [54][55][56][57][58][59]. By comparison with the literature results [8][9][10][11][12] of the activity of uranyl complexes as anticancer agents for many different cell lines, it was found that the Schiff's base uranyl complexes that were prepared in this study have more effective IC50, which indicated less toxicity than previously reported results, which may be because this is the first study that investigated their effect against ovarian cancer and melanoma cell lines.…”
Section: Anticancer and Toxicological Studiesmentioning
confidence: 54%
“…The results clarified that uranyl complexes show better anticancer activities than ligands when both cells are examined [54][55][56][57][58][59]. By comparison with the literature results [8][9][10][11][12] of the activity of uranyl complexes as anticancer agents for many different cell lines, it was found that the Schiff's base uranyl complexes that were prepared in this study have more effective IC50, which indicated less toxicity than previously reported results, which may be because this is the first study that investigated their effect against ovarian cancer and melanoma cell lines.…”
Section: Anticancer and Toxicological Studiesmentioning
confidence: 54%
“…Table 3 lists the estimated quantum chemical factors. The Equations (1)–(8) below were used to derive further characteristics such as E, absolute electronegativities, chemical potentials, Pi, absolute hardness, absolute softness, global electrophilicity, global softness, S, and additional electronic charge, N max [ 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…A tetradentate Schiff base ligand ( Figure 35 ) was coordinated with La(III) [ 127 ]. Both substances were tested for antiproliferative activity against MCF-7 and HepG2 (SRB, 48h exposure) and yielded promising results (IC 50 = 23–50 μM).…”
Section: Novel Metal Complexes In Cancer Therapymentioning
confidence: 99%